2009
DOI: 10.1016/j.jmb.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ATP-Driven PCNA Clamp Loading by S. cerevisiae RFC

Abstract: Circular clamps tether polymerases to DNA, serving as essential processivity factors in genome replication, and function in other critical cellular processes as well. Clamp loaders catalyze clamp assembly onto DNA, and the question of how these proteins construct a topological link between a clamp and DNA remains open, especially the mechanism by which ATP is utilized for the task. Here we describe pre-steady state analysis of ATP hydrolysis, PCNA clamp opening and DNA binding by S. cerevisiae RFC, and present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
100
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(110 citation statements)
references
References 34 publications
9
100
0
Order By: Relevance
“…This enzyme superfamily has functionally diverse roles that include not only RNA and DNA helicases, proteases, chaperones, and metal chelatases but many additional DNA replication factors such as processivity clamp loaders (e.g., replication factor C [38] and the ␥ complex [116]), initiator proteins (e.g., DnaA and the origin recognition complex [72]), and helicase loaders (e.g., DnaC [57] and Cdc6 [152]). The Mcm proteins, in common with many members of this group, oligomerize into ring-shaped (i.e., toroidal) complexes (23,193) and use ATP binding and hydrolysis to manipulate a substrate (e.g., DNA) within their central channels.…”
Section: The Eukaryotic MCM Genes Define Six Families Of Aaa ؉ Motor mentioning
confidence: 99%
“…This enzyme superfamily has functionally diverse roles that include not only RNA and DNA helicases, proteases, chaperones, and metal chelatases but many additional DNA replication factors such as processivity clamp loaders (e.g., replication factor C [38] and the ␥ complex [116]), initiator proteins (e.g., DnaA and the origin recognition complex [72]), and helicase loaders (e.g., DnaC [57] and Cdc6 [152]). The Mcm proteins, in common with many members of this group, oligomerize into ring-shaped (i.e., toroidal) complexes (23,193) and use ATP binding and hydrolysis to manipulate a substrate (e.g., DNA) within their central channels.…”
Section: The Eukaryotic MCM Genes Define Six Families Of Aaa ؉ Motor mentioning
confidence: 99%
“…The clamp is loaded onto DNA by the clamp loader, a five-subunit complex of AAAϩ family proteins that couple ATP binding and hydrolysis to mechanical work (8 -13). Structural and mechanistic analyses of clamp loaders such as E. coli ␥ complex (11,14), bacteriophage T4 gp44/62 (8,15,16), and Saccharomyces cerevisiae RFC (10,(17)(18)(19) among others, have shown that ATP binding enables the clamp loader to bind and open the clamp and bind ptDNA, and ATP hydrolysis leads to the release of the clamp-ptDNA product (see Fig. 1A), which can then be used by DNA polymerase and other proteins.…”
mentioning
confidence: 99%
“…1A), which can then be used by DNA polymerase and other proteins. In recent pre-steady state kinetic studies of S. cerevisiae RFC and PCNA, we explicitly measured the rates of individual steps in the reaction, including PCNA opening/closing, ptDNA binding/release, ATP hydrolysis, and phosphate (P i ) release (17,18). The data revealed a pair of slow events that bookend the loading reaction: the first occurs after ATP binding to RFC (RFC acti-vation) and involves conformational changes that enable PCNA opening and ptDNA binding to form an RFC-ATP-PCNA openptDNA intermediate primed for ATP hydrolysis; the second occurs after ATP hydrolysis (RFC deactivation) and involves conformational changes that enable PCNA closure and release of the PCNA-ptDNA product.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of ATPγS the RFC · PCNA complex opened the clamp and bound to DNA but ring closure was not completed (19,20). Pre-steady-state global analysis of the accompanying ATP hydrolysis showed that the ATPase reaction proceeded through multiple steps within two distinct phases; first, assembly of the RFC · PCNA · DNA complex was coupled to ATP binding and second disassembly was coupled to ATP hydrolysis (21). Completion of a functioning holoenzyme requires addition of polδ to the RFC · PCNA · DNA complex.…”
mentioning
confidence: 99%